The Use of Short Stories as Learning Media for Character Education for Elementary School Students during the Covid-19 Pandemic - Agniya Lutfia Fahrannisa; M Muktiarni; Jonah Mupita (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to find out whether short stories can affect the attitudes and behavior of a child related to efforts to prevent the transmission of the COVID-19 virus. The research was conducted using descriptive qualitative methods to 10 elementary school students 3 Pagerwangi. The results show that learning with short stories media can influence children's attitudes and behavior. There is an increase in student behavior in an effort to prevent the transmission of the COVID-19 virus. Some students who previously lacked an understanding of health protocols, have better understood how important it is to obey health protocols, and also always do it in their daily lives. This can be seen from the decrease in students who are negligent in carrying out health protocols. Learning through this short story media, students are expected to further improve efforts to prevent the transmission of the COVID-19 virus in their daily lives, as well as remind each other the importance of carrying out health protocols correctly for others.